Communities and households in the greater American Southwest: new perspectives and case studies - Stokes, Robert J., editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2019)
New research on human organization in the American Southwest, examining families, households, and communities in the Ancestral Puebloan, Mogollon, and Hohokam cultural areas from the earliest habitation to the twenty-first century. Using historical data, dialectic approaches, problem-oriented and data-driven analysis, and ethnographic and gender studies methodologies.--Provided by publisher.
Communities and households in southwestern archaeology: historical and theoretical perspectives / Robert J. Stokes -- Household action, communal ritual, and treachery in the ridges basin community / James M. Potter -- The rapidly evolving household: episodic change at Chodistas and Grasshopper Pueblos, Arizona / Stephanie M. Whittlesey and J. Jefferson Reid -- The role of landless families and households in the creation of new pueblo communities in the Mimbres area during the classic period / Robert J. Stokes -- Social distancing and fragmentation: the 150-year-long transition to the Hohokam classic period in the Tucson Basin, southern Arizona / Henry D. Wallace and Michael W. Lindeman -- Pliant communities: commonalities between snowbirds and seasonal mobile group visitation at the Eastern Frontier Pueblos / Deni J. Seymour -- Those who stayed behind: enclaved Lipan Apache communities / Oscar Rodriguez and Deni J. Seymour -- Pithouse community development at the Harris Site, southwestern New Mexico / Barbara J. Roth -- Houses, public architecture, and the organization of Fremont communities / Katie K. Richards, James R. Allison, Lindsay D. Johansson, Richard K. Talbot, and Scott M. Ure -- Integrating households and communities at Jornada Mogollon Pueblos / Myles R. Miller -- Household, community, and circular pueblos in the American Southwest: a case study from the Salinas Region of central New Mexico / Alison R. Rautman -- An analysis of three Pueblo II Period great house communities of the southern Cibola sub-region / Kristin N. Safi and Andrew I. Duff.
Keywords: Indians of North America -- Southwest, New -- Antiquities; Households -- Southwest, New -- History; Excavations (Archaeology) -- Southwest, New; Southwest, New -- Antiquities; Southwest, New -- Social conditions; Household archaeology -- Southwest, New -- Case studies